2016
DOI: 10.1167/iovs.15-18593
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Genetic Risk Profile of the Rapidly Progressing Diffuse-Trickling Subtype of Geographic Atrophy in Age-Related Macular Degeneration (AMD)

Abstract: Citation: Fleckenstein M, Grassmann F, Lindner M, et al. Distinct genetic risk profile of the rapidly progressing diffuse-trickling subtype of geographic atrophy in age-related macular degeneration (AMD). Invest Ophthalmol Vis Sci. 2016;57:246357: -247157: . DOI:10.1167 PURPOSE. To genetically characterize a subphenotype of geographic atrophy (GA) in AMD associated with rapid progression and a diffuse-trickling appearance on fundus autofluorescence imaging. METHODS.Patients from the Fundus Autofluorescence in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…6 7 GA progression was shown to be associated with perilesional phenotypes in fundus autofluorescence (FAF) imaging which exhibit to some degree a distinct genetic risk profile, especially with regard to the ARMS2 risk allele and the diffuse-trickling FAF pattern. 8 In the context of iAMD, other studies have also demonstrated an association of this genetic risk variant with reticular pseudodrusen (RPD), an ocular iAMD biomarker substantially impacting the risk for conversion into advanced disease stages. [9][10][11] However, only little is known about the prognostic relevance of structural iAMD phenotypes across different, that means from early to advanced, disease stages since most studies in early or iAMD exclude data once the study outcome, development of late-stage AMD, is reached.…”
Section: Introductionmentioning
confidence: 99%
“…6 7 GA progression was shown to be associated with perilesional phenotypes in fundus autofluorescence (FAF) imaging which exhibit to some degree a distinct genetic risk profile, especially with regard to the ARMS2 risk allele and the diffuse-trickling FAF pattern. 8 In the context of iAMD, other studies have also demonstrated an association of this genetic risk variant with reticular pseudodrusen (RPD), an ocular iAMD biomarker substantially impacting the risk for conversion into advanced disease stages. [9][10][11] However, only little is known about the prognostic relevance of structural iAMD phenotypes across different, that means from early to advanced, disease stages since most studies in early or iAMD exclude data once the study outcome, development of late-stage AMD, is reached.…”
Section: Introductionmentioning
confidence: 99%
“…a rapidly progressing autofluorescence phenotype, which was previously shown to exhibit a distinct genetic risk profile). 23 , 51 Their training accuracies ranged from 0.98 to 0.99, whereas validation accuracies ranged from 0.77 to 0.96. Keenan et al 24 generated three binary GA-related classification models using CFP and CNN: a GA detection, a central-GA detection, and a centrality detection model.…”
Section: Resultsmentioning
confidence: 99%
“…For example, choroidal insufficiency has been previously implicated in the pathogenesis of subphenotypes within the spectrum of AMD including ''reticular macular disease'' and ''diffuse-trickling geographic atrophy'' based on indocyanine green and fluorescein angiography findings, pronounced choroidal thinning, and cardiovascular comorbidity. [33][34][35][36][37] Limitations of this study need to be considered. While STGD1 and AMD patients exhibited phenotypic differences inside of RPE atrophy, these differences appeared to be not adequately quantified by the AFS area fraction.…”
Section: Discussionmentioning
confidence: 98%
“…To avoid potential confounding, patients exhibiting ''diffusetrickling geographic atrophy'' were not included, as choroidal insufficiency has been previously implicated in the pathogenesis. [33][34][35][36][37] Genetic testing was conducted at the Institute of Human Genetics, University of Regensburg (n ¼ 7), and at the Center for Human Genetics Bioscientia, Ingelheim (n ¼ 6). Analysis of all coding exons of the ABCA4 and PRPH2 genes was done by either direct chain-terminating dideoxynucleotide Sanger sequencing, a custom-designed GeneChip CustomSeq Resequencing Array (RetChip; Affymetrix, Santa Clara, CA, USA), or next-generation sequencing (Regensburg, n ¼ 5; Bioscientia, n ¼ 6).…”
Section: Patient Characterizationmentioning
confidence: 99%